Lucerne improves some sustainability indicators but may decrease profitability of cropping rotations on the Jimbour Plain - Murray-Prior, Roy; Whish, J.; Carberry, P.; Dalgleish, N. (CSIRO Publishing, 2005)
Long-run rotational gross margins were calculated with yields derived from biophysical simulations in a crop simulation model over a period of 100 years and prices simulated in @Risk based on subjective triangular price distributions elicited from the Jimbour Plain farmer group. Rotations included chickpeas, cotton, lucerne, sorghum, wheat and different lengths of fallow. The aim was to assess the profitability of rotations with and without lucerne. Output presented to the farmers included mean annual gross margins and distributions of gross margins with box and whisker plots found to be suitable. Mean-standard deviation and first and second-degree stochastic dominance efficiency measures were also calculated. The paper outlines a method for combining biophysical and price simulations that can be understood by farmers. Including lucerne in the rotations improved some sustainability indicators but reduced profitability.